2015
DOI: 10.1007/s10709-015-9820-y
|View full text |Cite
|
Sign up to set email alerts
|

First insight into divergence, representation and chromosome distribution of reverse transcriptase fragments from L1 retrotransposons in peanut and wild relative species

Abstract: Peanut is an allotetraploid (2n = 2x = 40, AABB) of recent origin. Arachis duranensis and A. ipaënsis, the most probable diploid ancestors of the cultigen, and several other wild diploid species with different genomes (A, B, D, F and K) are used in peanut breeding programs. However, the genomic relationships and the evolutionary pathways of genome differentiation of these species are poorly understood. We performed a sequence-based phylogenetic analysis of the L1 reverse transcriptase and estimated its represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 76 publications
1
25
2
1
Order By: Relevance
“…However, the A and B subgenomes appear to have undergone relatively few changes since polyploidization: genomic in situ hybridization (GISH), using genomic DNA from the diploid species as probes, clearly distinguishes A and B chromosomes and does not show large A-B mosaics 7,8 . Also, the genome size of A. hypogaea is close to the sum of those for A. duranensis and A. ipaensis (1.25 and 1.56 Gb, respectively 14 ), indicating that there has been no large change in genome size since polyploidy. Most notably, observations of progeny derived from crosses between cultivated peanut and an artificially induced allotetraploid A. ipaensis K30076 × A. duranensis V14167 (2n = 4x = 40) 15 strongly support the close relationships between the diploid genomes and the corresponding The genome sequences of Arachis duranensis and Arachis ipaensis, the diploid ancestors of cultivated peanut and were numbered according to previously published linkage maps 17,19,23,24 .…”
Section: Openmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the A and B subgenomes appear to have undergone relatively few changes since polyploidization: genomic in situ hybridization (GISH), using genomic DNA from the diploid species as probes, clearly distinguishes A and B chromosomes and does not show large A-B mosaics 7,8 . Also, the genome size of A. hypogaea is close to the sum of those for A. duranensis and A. ipaensis (1.25 and 1.56 Gb, respectively 14 ), indicating that there has been no large change in genome size since polyploidy. Most notably, observations of progeny derived from crosses between cultivated peanut and an artificially induced allotetraploid A. ipaensis K30076 × A. duranensis V14167 (2n = 4x = 40) 15 strongly support the close relationships between the diploid genomes and the corresponding The genome sequences of Arachis duranensis and Arachis ipaensis, the diploid ancestors of cultivated peanut and were numbered according to previously published linkage maps 17,19,23,24 .…”
Section: Openmentioning
confidence: 85%
“…1-12) and were numbered according to previously published linkage maps 17,19,23,24 . They represent 82% and 86% of the genomes, respectively, when considering genome size estimates based on flow cytometry 14,25 , or 95% and 98% of the genomes when using estimates derived from k-mer frequencies with k = 17 ( Supplementary Figs. 13 and 14).…”
Section: Sequencing and Assembly Of The Diploid A And B Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FISH experiments in Cannabis sativa suggested that differential accumulation of LINE retrotransposon elements onto the Y chromosome leads to sex chromosome heteromorphism [53]. Although the chromosomal distribution of LINEs has been analyzed in only a few plant species, the FISH results here revealed that the distribution of LINEs in mulberry chromosomes was similar to that in sugar beet and peanut chromosomes [28] [54]. Furthermore, the weak hybridization signals observed in this study indicated that LINEs were not abundant in the mulberry genome (Figure 4).…”
Section: Chromosomal Localization Of Line Retrotransposonsmentioning
confidence: 53%
“…The rt is a key enzyme for retrotransposition and shares several conserved domains that are typical of retroviral RNA-directed DNA polymerases [24]. Previously studies have suggested that amplification of rt fragments using degenerate oligonucleotide primers complementary to the conserved domains of the rt is a feasible and efficient approach to evaluate the characterization of LINE retrotransposons in various plant species [18] [25] [26] [27] [28].…”
Section: Introductionmentioning
confidence: 99%